2008
DOI: 10.1007/s00737-008-0013-x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal depression and filicide—case study of ten mothers

Abstract: This study describes ten cases of filicides committed by mothers who intentionally killed one or more of their children within 12 months after delivery. The data were collected from police and court records, forensic psychiatric records, autopsy reports, and other medical records. The mean age of the mothers was 28.5 years and of the victims 4 months. The symptoms of depression were clear: an irritable, severely depressed mood with crying spells, insomnia, fatigue, anxiety, preoccupation with worries about the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 25 publications
2
26
0
3
Order By: Relevance
“…As with depression outside of the perinatal period, postpartum depression often co‐occurs with other psychiatric disorders, the most common being generalized anxiety disorder, obsessive‐compulsive disorder, social phobia and agoraphobia (Figueira, Fernandes Malloy‐Diniz, Aurélio Romano‐Silva, Silva Neves, & Corrêa, 2009). In some rare cases, postpartum depression has been linked to suicidality and filicide (Kauppi, Kumpulainen, Vanamo, Merikanto, & Karkola, 2008; Paris, Bolton, & Weinberg, 2009). Alarmingly, studies have also shown that as many as 50% of postpartum depression cases are undiagnosed (Chaudron et al, 2005; Murray, Woolgar, Murray, & Cooper, 2003), and reasons for this statistic include lack of attention on the mental health of the mother by health care providers as well as under‐reporting of symptoms by the mother herself.…”
Section: Maternal Behavior Is Affected By Concurrent Mood or Deprmentioning
confidence: 99%
“…As with depression outside of the perinatal period, postpartum depression often co‐occurs with other psychiatric disorders, the most common being generalized anxiety disorder, obsessive‐compulsive disorder, social phobia and agoraphobia (Figueira, Fernandes Malloy‐Diniz, Aurélio Romano‐Silva, Silva Neves, & Corrêa, 2009). In some rare cases, postpartum depression has been linked to suicidality and filicide (Kauppi, Kumpulainen, Vanamo, Merikanto, & Karkola, 2008; Paris, Bolton, & Weinberg, 2009). Alarmingly, studies have also shown that as many as 50% of postpartum depression cases are undiagnosed (Chaudron et al, 2005; Murray, Woolgar, Murray, & Cooper, 2003), and reasons for this statistic include lack of attention on the mental health of the mother by health care providers as well as under‐reporting of symptoms by the mother herself.…”
Section: Maternal Behavior Is Affected By Concurrent Mood or Deprmentioning
confidence: 99%
“…Antenatal depression is considered as a major risk factor for postpartum depression, both of which are associated with an increased risk of suicide during the perinatal period and an increased risk of infanticide in the postpartum period (Level of Evidence 3 and 4, Table 1) [6][7][8][9][10]. Despite a widespread idea, pregnancy does not protect against depression and it may even be associated with behaviors that put mother and child at risk.…”
Section: Impact Of Depression On the Mother And Childmentioning
confidence: 99%
“…Possible motives for neonaticide included altruism, revenge, undesirable or unwanted child, psychiatric disorders and accidentally manslaughter [6,12]. Postpartum depression is contributed to infanticide [13][14][15]. Maybe it is a reasonable interpretation for neonaticide, but the previous studies revealed that unwanted child was the main motive for neonaticide rather than postpartum depression [4,6,12].…”
Section: Introductionmentioning
confidence: 91%
“…Infanticides are often assumed to be linked to postpartum depression or psychosis, or other mental illnesses such as Munchausen by proxy syndrome [12][13][14][15]. The 20 offenders' mental status was normal based on the materials we used.…”
Section: Discussionmentioning
confidence: 99%